AUTOMATION OF THE PROCESS OF CONVERTING CURRENCIES INTO ROUBLES ON THE BASIS OF TELEGRAM - Aynaz L. Nazmeev; Gulnara A. Gareeva; Diana R. Grigoreva; Bulat R. Karimullin; Evelina M. Kuznetsova (International Journal of Advanced Studies, 2023)
This article describes the creation of a Telegram bot that will help us quickly convert any currency into rubles. The main thing for the user will be the simplicity and speed of using this bot. And to a large extent it simplifies the work for many employees who often have to convert foreign currency into rubles.